Pengaruh Rebusan Daun Pepaya Terhadap Nyeri Dismenorea Pada Wanita Usia Subur (WUS) - Editiya, Vidya Sri; Sunarsih, Sunarsih; Yantina, Yuli (MIDWIFERY JOURNAL, 2024)
Background : dysmenorrhoea is pain during menstruation generally with cramps and centralized in the lower abdomen. Dysmenorrhea can be divided into two groups, primary dysmenorrhea is menstrual pain that has lasted since menarche and there is no abnormality in the uterus, while secondary dysmenorrhea is menstrual pain that occurs due to gynecologic disorders such as endometriosis (mostly), fibroids, adenomyosis. There are 2 treatments for menstrual pain (dysmenorrhea) namely pharmacological and non-pharmacological. One of the non-pharmacological treatments is drinking papaya leaf decoction. Papaya leaves contain vitamin E which can reduce the level of menstrual pain through inhibition of prostaglandin biosynthesis.Purpose : To determine the effect of papaya leaf decoction on dysmenorrhea pain in women of fertile age (WUS) in Keteguhan Village, Telukbetung Timur District, Bandar Lampung.Methods : This study used a pre-experimental design with a One Group Pretest Posttest approach. The sample consisted of 30 respondents where this research was conducted from April-July 2021. Data collection used the Numeric Rating Scale instrument. The statistical used was test the Wilcoxon test.Results : From the results of the research conducted by the author, the mean score of dysmenorrheal pain before administration of papaya leaf decoction was 5.73 while the mean score of dysmenorrhoea pain after administration of papaya leaf decoction was 3.27.Conclusion : The p-value obtained is 0.000, it can be concluded that there is an effect of papaya leaf decoction on dysmenorrhea pain in women of fertile age (WUS) in Keteguhan Village, Telukbetung Timur District, Bandar Lampung. Keywords : Papaya Leaves, Menstrual Pain, Dysmenorrhea ABSTRAK Latar Belakang : Dismenorea merupakan nyeri saat haid yang umumnya dengan rasa kram serta terpusat di abdomen bawah. Dismenorea dapat dibagi jadi dua kelompok, dismenorea primer merupakan nyeri haid yang berlangsung sejak menarche serta tidak ada kelainan pada alat kandungan, sedangkan dismenorea sekunder merupakan nyeri haid yang terjadi karena kelainan ginegologik misalnya: endometriosis (sebagian besar), fibroids, adenomyosis. Penanganan nyeri haid (dismenorea) ada 2 yaitu secara farmakologi serta nonfarmakologi. Salah satu penanganan dengan cara nonfarmakologi adalah dengan meminum rebusan daun pepaya. Daun Pepaya mengandung vitamin E yang dapat mengurangi tingkat nyeri haid melalui hambatan terhadap biosintesis prostaglandin.Tujuan : Untuk mengetahui pengaruh rebusan daun pepaya terhadap nyeri dismenorea pada wanita usia subur (WUS) Di Kelurahan Keteguhan Kecamatan Telukbetung Timur Bandar LampungMetode : Penelitian ini menggunakan rancangan Praeksperimen dengan pendekatan One Grup Pretest Posttest. Sampel berjumlah 30 orang responden dimana penelitian ini dilakukan dari bulan April-Juli 2021. Pengumpulan data menggunakan instrumen Numeric Rating Scale (NRS). Uji statistik yang digunakan uji wilcoxon.Hasil : Dari hasil penelitian yang dilakukan oleh penulis adalah rerata score nyeri dismenorea sebelum pemberian rebusan daun pepaya 5,73 sedangkan rerata score nyeri dismenorea sesudah pemberian rebusan daun pepaya 3,27.Kesimpulan : Hasil p-value diperoleh 0,000, maka dapat disimpulkan ada pengaruh rebusan daun pepaya terhadap  nyeri dismenorea pada wanita usia subur (WUS) Di Kelurahan Keteguhan Kecamatan Telukbetung Timur Bandar Lampung. Kata Kunci : Daun Pepaya, Nyeri haid, Dismenorea